PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI LINGKUNGAN SD NEGERI 001 SEKUPANG - Wika Widyastuti; Hazriyanto; Hendri Kremer (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
The research aims to know the influence of leadership, job motivation and job discipline on the performance of civil servants in the 001 Sekupang State Elementary School. The study used census methods, namely dataring the entire existing population. Based on the census in the field, then samples in the study were as many as 33 employees. Data is collected by questionnaire technique. In the results of this study there was a significant regression equation Y = 8,600 + 0,712X1 + 0.406X2 + 0.236X3+ e. Leadership variable there was a significant direct influence of n on employee performance with a coefficient value of 0.419, Work Motivation Variables there was a significant direct influence on employee performance with a coefficient value of 0.422, variables of 0. job discipline there is a significant direct influence of job discipline on employee performance with a coefficient value of 0.426. as well as leadership variables, job motivation and the discipline of simultaneous influential work on employee performance with R2 value of 76.8%. while the rest of the amount of 23.2% is being presented by other variables that do not enter the study.